A general and inexpensive protocol for the Cu-catalyzed C–S cross-coupling reaction between aryl halides and thiols. Issue 47 (25th November 2015) - Thomas, Anns Maria; Asha, Sujatha; Sindhu, K.S.; Anilkumar, Gopinathan
Graphical abstract: Abstract: A cost effective and easily available CuI/DABCO catalytic system has been developed for C–S cross-coupling reaction. This method is extremely useful for the thioetherification of aryl and heteroaryl halides providing excellent yields and good chemoselectivity.